Analisis Konsep Pemenuhan Pelayanan Publik Pada Local Government Di Era Otonomi Daerah (Studi Kasus Kota Surabaya) - Vidya Imanuari Pertiwi (Program Studi Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Warmadewa, 2023)
Regional autonomy in Indonesia is not a new concept that has been implemented. Based on the track record of the previous prevailing laws and regulations, Indonesia officially defined autonomy in Law No. 22/1999 with a dominant focus on decentralization. However, in line with the implementation of autonomy itself, it is said that there are still many problems or even not in line with expectations. This study focuses on the concept of regional autonomy used in efforts to fulfill public services, the weaknesses of related concepts and examples of successful regions in Indonesia that implement regional autonomy. The research method used is qualitative with secondary data or secondary data in data collection. The results of the study are that regions in Indonesia have a tendency to use the concept of traditional bureaucratic authority, where the Indonesian government provides services without involving other parties. The weakness of the concept or model lies in the reach of the local government on all matters of public service itself. Regional limitations are the main factor for these weaknesses, as a result of all forms of public services being developed by the local government without involving the community and the private sector. The city of Surabaya is a successful example of fulfilling public services using E-Government